Response of the intertropical convergence zone to zonally asymmetric subtropical surface forcings. Issue 22 (19th November 2015) - Shaw, Tiffany A.; Voigt, Aiko; Kang, Sarah M.; Seo, Jeongbin
Abstract: The energetic framework predicts no shift of the zonal mean Intertropical Convergence Zone (ITCZ) in response to zonally asymmetric forcings (zonal warming and cooling regions with zero zonal mean) assuming radiative feedbacks are linear. Here we show the ITCZ shifts southward in response to a zonally asymmetric forcing in the Northern Hemisphere subtropics in a slab ocean aquaplanet model. The southward shift is consistent with decreased zonal mean energy input to the atmosphere due to cloud radiative effect changes in the cooling region. When cloud‐radiative feedbacks are disabled the ITCZ shifts northward consistent with changes in the warming region where increased energy input via surface heat fluxes and stationary Rossby‐wave transport dominate. Competition between cooling and warming regions leads to changes in gross moist stability. Our results show rectification of zonally asymmetric forcings play an important role in zonal mean ITCZ dynamics and highlight the importance of assessing the momentum budget when interpreting ITCZ shifts. Key Points: Energetic framework predicts no shift of ITCZ to zonally asymmetric forcing Opposite ITCZ shifts for radiative feedbacks and surface heat fluxes Momentum budget can be used to infer robustness of energetic framework